2017
DOI: 10.1186/s12958-017-0305-y
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular characterization of gametogenic progression in ex vivo cultured prepuberal mouse testes

Abstract: BackgroundRecently, an effective testis culture method using a gas-liquid interphase, capable of differentiate male germ cells from neonatal spermatogonia to spermatozoa has been developed. Nevertheless, this methodology needs deep analyses that allow future experimental approaches in basic, pathologic and/or reprotoxicologic studies. Because of this, we characterized at cellular and molecular levels the entire in vitro spermatogenic progression, in order to understand and evaluate the characteristics that def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…The method is quite simple in that immature testis tissue pieces were placed on the agarose gel block which was half‐soaked in the culture media. This agarose gel culture method (AG) was repeated by several researchers and became a reliable culture method for in vitro spermatogenesis . However, the efficiency and duration of in vitro spermatogenesis were not comparable to those in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…The method is quite simple in that immature testis tissue pieces were placed on the agarose gel block which was half‐soaked in the culture media. This agarose gel culture method (AG) was repeated by several researchers and became a reliable culture method for in vitro spermatogenesis . However, the efficiency and duration of in vitro spermatogenesis were not comparable to those in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Both KSR and AlbuMAX are capable of inducing complete spermatogenesis in mouse testis tissues during the neonatal or fetal period [ 9 ]. Other research groups also reported that spermatogenesis was promoted in testis organ culture using medium containing either KSR or AlbuMAX in mice [ 10 , 11 , 12 , 13 , 14 ]. According to the manufacturing company, KSR includes 83 mg/mL of AlbuMAX [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The agarose gel organ culture method became a reliable standard method, repeated by many independent research groups, to induce mouse spermatogenesis. [42][43][44][45] However, the efficiency and duration of the spermatogenesis were far from comparable to those observed in vivo. 46 To improve the culture condition, replicating the microcirculatory system of the body in the organ culture system could be effective.…”
Section: Microfluidic Systemmentioning
confidence: 89%
“…The agarose gel organ culture method became a reliable standard method, repeated by many independent research groups, to induce mouse spermatogenesis . However, the efficiency and duration of the spermatogenesis were far from comparable to those observed in vivo .…”
Section: Organ Culture Method Modern Developmentmentioning
confidence: 99%